Exploration of consumer behavior changes post-pandemic in the tourism sector - Novi Hidayah; Marshella Aprillia Setiawan; Ridho Arrozaq Nur Ramadhan; Mochammad Revaldo Pangestu; Abdurrazak Afifi; Yuningsih Yuningsih (Borneo Novelty Publishing, 2025)
Purpose - The purpose of this research is to identify new behavioral patterns that have emerged post-pandemic, particularly focusing on how the COVID-19 pandemic has impacted consumer behavior in the tourism sector. Methodology/Design/Approach - The study examines changes in consumer behavior following the COVID-19 pandemic, specifically looking at the increased interest in domestic travel, preferences for nature and outdoor tourism, and heightened awareness of health and safety protocols while traveling. Finding - The study found that there has been a noticeable shift in tourism dynamics, with consumers now prioritizing sustainable travel, safety, flexibility in cancellations, and environmental sustainability. These changes have forced tourism industry players to adapt to new consumer preferences, requiring them to develop more flexible strategies to meet the emerging trends.Originality/Value - This research highlights the need for the tourism sector to adapt its marketing and service strategies to accommodate the post-pandemic shift in consumer behavior. By understanding these new preferences, the industry can better retain and attract consumers in the evolving tourism landscape.